Candida parapsilosis Infection after Lumbosacral Arthrodesis with a PEEK TLIF Interbody Fusion Device: Case Report - Wajchenberg, Marcelo (Thieme Revinter Publicações Ltda., 2021)

(untitled) (Rev Bras Ortop (Sao Paulo))
Spondylodiscitis is an uncommon but serious complication after spine surgeries, and its main etiologic agent is Staphylococcus aureus . Fungal infections are rare and mostly caused by Candida albicans . We report the clinical case of a 69-year-old male patient who underwent a L2-S1 arthrodesis for degenerative scoliosis correction. He presented an infection 2.5 months after the procedure, a spondylodiscitis at L5-S1 levels, caused by Candida parapsilosis . The treatment consisted of surgical material removal, tricortical iliac graft placement in an anterior approach (L5-S1), lumbopelvic fixation (from T10 to the pelvis) in a posterior approach, and drug treatment with anidulafungin and fluconazole. This last medication was administered for 12 months, with good clinical outcomes.